The adoption of artificial intelligence technology for talent acquisition of virtual assistants in Metro Manila - Alfonso, Jovy P. Antonio, Cristil T. Mendoza, Liezel E. Sales, Andrea Nicole B. Santos, Aisleen P. 4 0 16; 5
ABSTRACT Artificial intelligence (AI) stands as a transformative force with the potential to reshape the landscape of management and organizational practices. This study delves into the adoption of Al technology for talent acquisition within the realm of virtual assistants in Metro Manila. Moving beyond a mere exploration of the relationship between behavioral intention to adopt Al and technology adoption factors, the research involved online survey questionnaires administered to thirty HR professionals across various companies. The results illuminate a generally positive perspective among HR professionals in Metro Manila towards the integration of Al in virtual assistant hiring. Their anticipation centers around improved efficiency, accuracy, fairness, and an enhanced candidate experience. This research significantly contributes to ongoing discussions about Al's transformative impact on talent acquisition processes for virtual assistants, providing practical insights that can guide organizations navigating this evolving landscape. However, it is essential to acknowledge the study's limitations, as it offers a focused perspective on seven specific companies within the Metro Manila area, potentially not providing a comprehensive overview of the entire virtual assistant industry. Furthermore, the scope of the study is confined to the implementation of Al in the pre-assessment process, excluding a comprehensive examination of the entire recruitment procedure. Keywords: artificial intelligence (AI), talent acquisition, virtual assistants, technology adoption factors, behavioral intention, human resource professionals, Al integration.
Business Research: (BSBA major in Human Resource Management) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2